BALKON PINTAR KREATIF BERKONSEP COMPULSORY EDUCATION DESA KOA KECAMATAN MOLLO BARAT PROVINSI NUSA TENGGARA TIMUR (TTS) - Ivo Basri K; Budi Kurniawan; Elisabeth E. Fernandes; Muffaridun Balangga; Salfian Ismail Dede (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
Creative Smart Balcony with Compulsory Education Concept is a mini building that was built and established as a place or place to store learning media as well as a place for the people of Koa Village to create a good and comfortable learning ecosystem. The teaching and learning process requires an intermediary tool or commonly called learning media. Learning media is basically a tool in the teaching and learning process that is able to facilitate teachers in conveying material so that students are able to understand the material presented by the teacher and facilitate the process of transferring knowledge. In addition to learning media, there are hard skills, soft skills and life skills that must be mastered and developed by students and society in general. Such as mastering technology, communicating properly and correctly, being able to think critically, being able to solve problems and make decisions, managing time as much as possible, skills to improve internal control centers, group work skills and many other skills.